Ensuring Sustainable Access to Drinking Water in Sub Saharan Africa: Conflict Between Financial and Social Objectives. (December 2015) - Marson, Marta; Savin, Ivan
Highlights: The study models the dynamics in water coverage of utilities in Sub Saharan Africa. It addresses conflict between performance-based incentives and social objectives. Water access increases for relatively low levels of capital cost recovery. Water access however deteriorates for higher levels of capital cost recovery. Cost-recovery targets for SSA utilities should be lower than generally recommended. Summary: We study a model explaining dynamics in water coverage that accounts for financial performances of utilities. Our dataset covers 25 Sub-Saharan countries from 1996 to 2012. Results suggest that access to water depends upon financial results, but this relationship is not linear: we find important access increases for relatively low levels of capital cost recovery and deterioration of access performances beyond a certain threshold. Our results are consistent with the literature about risks of corporatization and potential conflict between financial and social objectives in the water sector, and they provide supporting quantitative evidence and recommendations for sector policies in the region.